Principles of agonist recognition in Cys-loop receptors - Lynagh, Timothy; Pless, Stephan A. (Frontiers in Physiology, 2014)
Cys-loop receptors are ligand-gated ion channels that are activated by a structurally diverse array of neurotransmitters, including acetylcholine, serotonin, glycine and GABA. After the term “chemoreceptor” emerged over 100 years ago, there was some wait until affinity labeling, molecular cloning, functional studies and X-ray crystallography experiments identified the extracellular interface of adjacent subunits as the principal site of agonist binding. The question of how subtle differences at and around agonist-binding sites of different Cys-loop receptors can accommodate transmitters as chemically diverse as glycine and serotonin has been subject to intense research over the last three decades. This review outlines the functional diversity and current structural understanding of agonist-binding sites, including those of invertebrate Cys-loop receptors. Together, this provides a framework to understand the atomic determinants involved in how these valuable therapeutic targets recognize and bind their ligands.